A Colorimetric Method for Monitoring Tryptic Digestion Prior to Shotgun Proteomics. (10th February 2014) - Somiari, Richard I.; Renganathan, Kutralanathan; Russell, Stephen; Wolfe, Steven; Mayko, Florentina; Somiari, Stella B.
Abstract : Tryptic digestion is an important preanalytical step in shotgun proteomics because inadequate or excessive digestion can result in a failed or incomplete experiment. Unfortunately, this step is not routinely monitored before mass spectrometry because methods available for protein digestion monitoring either are time/sample consuming or require expensive equipment. To determine if a colorimetric method (ProDM Kit) can be used to identify the extent of tryptic digestion that yields the best proteomics outcome, plasma and serum digested for 8 h and 24 h were screened with ProDM, Bioanalyzer, and LC/MS/MS, and the effect of digestion on the number of proteins identified and sequence coverage was compared. About 6% and 16% less proteins were identified when >50% of proteins were digested in plasma and serum, respectively, compared to when 46% of proteins were digested. Average sequence coverage for albumin, haptoglobin, and serotransferrin after 2 h, 8 h, and 24 h digestion was 52%, 45%, and 45% for serum and 54%, 47%, and 42% for plasma, respectively. This paper reiterates the importance of optimizing the tryptic digestion step and demonstrates the extent to which ProDM can be used to monitor and standardize protein digestion to achieve better proteomics outcomes.